(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To summarize the major bioactive constituents and mechanisms of action of Phyllanthus amarus, and to synthesize the evidence regarding its effects on liver diseases, metabolic disorders, and renal–urinary conditions. Methods: A structured narrative review was conducted using international databases and selected Vietnamese medical journals up to 30 November 2025. Studies were included when they clearly identified the species or provided separate analysis for P. amarus, and described the preparation/intervention and outcome measures. Evidence was stratified into in vitro, animal, and human levels. Results: P. amarus contains lignans, polyphenols, flavonoids, tannins, and phenolic acids, and shows antioxidant, anti-inflammatory, immunomodulatory, hepatoprotective, and nephroprotective activities. Preclinical studies showed relatively consistent effects on HBV-related targets, toxic liver injury, insulin resistance, dyslipidemia, and calcium oxalate deposition. Human evidence remains limited and heterogeneous. A 1988 trial reported a high rate of HBsAg loss, but later studies did not reproduce this finding. Systematic reviews rated the certainty of evidence as low because of high risk of bias, mixing of different Phyllanthus species, and lack of product standardization. Short-term tolerability appears acceptable overall, but long-term safety and herb–drug interactions remain unclear. Conclusion: P. amarus should currently be regarded only as an adjunctive botanical and should not replace standard therapy. Further randomized double-blind trials using standardized preparations are needed to clarify efficacy and safety.